2022
DOI: 10.3390/biomedicines10123264
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Immunomodulatory Potential of Cow Colostrum Extracellular Vesicles (ColosEVs) in an Intestinal In Vitro Model

Abstract: Extracellular Vesicles (EVs) are nano-sized double-lipid-membrane-bound structures, acting mainly as signalling mediators between distant cells and, in particular, modulating the immune response and inflammation of targeted cells. Milk and colostrum contain high amounts of EVs that could be exploited as alternative natural systems in antimicrobial fighting. The aim of this study is to evaluate cow colostrum-derived EVs (colosEVs) for their antimicrobial, anti-inflammatory and immunomodulating effects in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…DEFB4A expression was also increased in another porcine ileum epithelial cell line (IPI-2I) after infection with S. typhimurium DT104 [26]. Furthermore, it was demonstrated that E. coli adhesion increases the expression of DEFB1 and DEFB4A in IPEC-J2 cells [95]. In this study, pre-treatment with OMWW-EP seemed to induce a return to the basal expression of DEFB1 (at the 0.35 µg dosage) and DEFB4A (at both dosages) after S. typhimurium infection, counteracting the effect of bacterial invasion and potentially restoring gut homeostasis.…”
Section: Discussionmentioning
confidence: 90%
“…DEFB4A expression was also increased in another porcine ileum epithelial cell line (IPI-2I) after infection with S. typhimurium DT104 [26]. Furthermore, it was demonstrated that E. coli adhesion increases the expression of DEFB1 and DEFB4A in IPEC-J2 cells [95]. In this study, pre-treatment with OMWW-EP seemed to induce a return to the basal expression of DEFB1 (at the 0.35 µg dosage) and DEFB4A (at both dosages) after S. typhimurium infection, counteracting the effect of bacterial invasion and potentially restoring gut homeostasis.…”
Section: Discussionmentioning
confidence: 90%
“…Since MEVs can alter the composition of the gut microbiota and their metabolite production, in turn, gut microbes can activate MEV signaling, suggesting a potential prebiotic role for MEVs [52,53]. Recent studies have indicated that bovine colostrum-derived EVs can regulate the host-pathogen interaction [54] and exert a specific antimicrobial effect against pathogens, such as E. Coli, by changing the cGAS/STING pathway, which is directly involved in the development of inflammation [55]. Thus, colostrum EVs can be used as an alternative antibiotic source for the treatment of calf neonatal diarrhea conditions.…”
Section: The Role Of Mevs In Gut and Intestine Healthmentioning
confidence: 99%